2000
DOI: 10.1523/jneurosci.20-01-00306.2000
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of On and Off Bipolar Cell Axonal Arbors in the Absence of Retinal Ganglion Cells

Abstract: Retinal cells that respond selectively to light onset or offset are segregated into On and Off pathways. Here, we describe the development of cone bipolar cells whose axonal arbors at maturity synapse onto ganglion cell dendrites confined to On and Off strata of the inner plexiform layer (IPL). In particular, we sought to determine whether the formation of this segregated pattern is dependent on the presence of ganglion cells. Developing bipolar cells were visualized using an antibody against recoverin, the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 47 publications
7
41
0
Order By: Relevance
“…The pattern and level of stratification of the axonal arbors of bipolar cells in the inner plexiform layer, which reflect their functional diversity, are not influenced by major changes in retinal architecture: the neonatal elimination of ganglion cells, which are their major target (Gunhan-Agar et al, 2000), the selective removal of cholinergic amacrine cells (Gunhan et al, 2002), the formation of supernumerary neurons in the inner nuclear layer (Strettoi and Volpini, 2002), or an imbalance in afferent activity (Bodnarenko et al, 1995), do affect the number of bipolar cells but not the connectivity in the ipl. Our data demonstrate that the lamination of rod bipolar cells, and probably the wiring of their axons, are not affected by the absence of their normal presynaptic partners.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern and level of stratification of the axonal arbors of bipolar cells in the inner plexiform layer, which reflect their functional diversity, are not influenced by major changes in retinal architecture: the neonatal elimination of ganglion cells, which are their major target (Gunhan-Agar et al, 2000), the selective removal of cholinergic amacrine cells (Gunhan et al, 2002), the formation of supernumerary neurons in the inner nuclear layer (Strettoi and Volpini, 2002), or an imbalance in afferent activity (Bodnarenko et al, 1995), do affect the number of bipolar cells but not the connectivity in the ipl. Our data demonstrate that the lamination of rod bipolar cells, and probably the wiring of their axons, are not affected by the absence of their normal presynaptic partners.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this idea, recent studies have shown that the axon terminals of On-and Off-cone bipolar cells form their stratified projection patterns in a remarkably precise manner, without any initial period of intermingling (Miller et al, 1999;Günhan-Agar et al, 2000). Moreover, electrophysiological recordings have reported that very few ganglion cells in the developing cat retina respond with On-Off discharges to flashing spots of light at a time when multistratified cells would be expected to be plentiful (Dubin et al, 1986;Tootle, 1993).…”
mentioning
confidence: 82%
“…The severe IPL phenotype seen in lak mutants contrasts with the relatively mild effects of GC ablation by optic nerve transection (Günhan-Agar et al, 2000;Williams et al, 2001). In the latter studies, GCs form but are experimentally killed in newborn rats or ferrets.…”
Section: Ac Projections To the Ipl Are Initially Guided By Cues From Gcsmentioning
confidence: 99%
“…Furthermore, it is unclear whether AC and BC axonal terminals are sculpted on a scaffold initially laid down by GC dendrites or are otherwise dependent on GC-derived cues. Günhan-Agar et al (Günhan-Agar et al, 2000) and Williams et al (Williams et al, 2001) showed that, in rats and ferrets, ACs and BCs develop and maintain ON and OFF stratification patterns after experimentally induced degeneration of GCs.…”
Section: Introductionmentioning
confidence: 99%